IDIOMS IN ENGLISH AND THEIR ALTERNATIVES IN UZBEK - Saminjonov Muhammadali Fardu (Galaxy International Interdisciplinary Research Journal, 2021)
The article lists idioms used in English and their Uzbek alternatives. In addition, the use of interlingual flexibility phrases is explained using examples.